Natural Background Level and Contamination of Shallow Groundwater Salinity in Various Aquifers in a Coastal Urbanized Area, South China. (9th August 2021) - Bi, Pan; Han, Dongya; Liu, Chunyan; Xiao, Liquan; Wu, Heqiu; Zhang, Meng
Abstract : Assessing natural background levels (NBLs) of chemical components in groundwater is useful for the evaluation of groundwater contamination in urbanized areas. The present study assessed the NBL of total dissolved solids (TDS) in various groundwater units in the Pearl River Delta (PRD) where urbanization is a large scale and discussed factors controlling groundwater salinity contamination in the PRD. Results showed that the NBL of TDS in groundwater in the coastal-alluvial plain was more than 1.5 times that in other groundwater units because of the seawater intrusion in this groundwater unit. By contrast, interactions of water and soils/rocks were the main factors controlling the NBLs of TDS in other groundwater units. Groundwater salinity contamination in the PRD was positively correlated with the urbanization level. Wastewater from township-village enterprises and industrial wastewater were likely to be the main sources for groundwater salinity contamination in the PRD. Moreover, the wastewater leakage from sewer systems was one of the main pathways for groundwater salinity contamination in urbanized areas, because the proportion of groundwater salinity contamination in urbanized areas formed in 1988–1998 was more than 1.5 times that in urbanized areas formed in 1998–2006 regardless of groundwater units. Besides, sewage irrigation and leakage of landfill leachate were also important sources for groundwater salinity contamination in the PRD.